The IL6 gene polymorphism −634C>G and IL17F gene polymorphism 7488T>C influence bone mineral density in young and elderly Japanese women - Oishi, Yoshie; Watanabe, Yoko; Shinoda, Shoko; Naka, Mamiko; Ozawa, Yoshiteru; Matsuyama, Takeshi; Morozumi, Kyoei; Fuke, Yoko (Gene, 2012)
Osteoporosis is an important public health problem because of the significant morbidity and mortality associated with its complications, particularly fractures. An important clinical risk factor in the pathogenesis of osteoporosis is the presence of genetic polymorphisms in susceptibility genes. However, few studies have investigated the relevance of these polymorphisms in premenopausal women. Recent studies have demonstrated interactions between bone and immune cells, and that cytokines produced by immune cells regulate bone turnover. In this study, we examined the associations between bone mineral density (BMD) and polymorphisms in genes encoding interleukin (IL)-6 (−634C>G; rs1800796), tumor necrosis factor (TNF)-α (−308G>A; rs1800629), IL-17F (7488T>C; rs763780), transforming growth factor (TGF)-β (869T>C; rs1800470), osteoprotegerin (OPG; 163A>G; rs3102735) and methylenetetrahydrofolate reductase (MTHFR; 677C>T; rs1801133) in young and elderly Japanese women. Whole-body, lumbar spine (L1 or L2–L4), and femoral neck BMD were measured in 100 young subjects (18–23years), and 100 elderly subjects (60–83years). Whole-body, lumbar spine, and femoral neck BMD were 1.13±0.06, 1.14±0.12, and 1.00±0.11g/cm2, respectively, in young subjects, and 0.92±0.09, 0.86±0.15, and 0.63±0.10g/cm2, respectively, in elderly subjects. The frequencies of the IL-6 CC, CG, and GG genotypes were 48%, 49%, and 3%, respectively. The frequencies of the IL17F TT, TC, and CC genotypes were 79%, 15%, and 6%, respectively, in young subjects. Polymorphisms of the IL-6 and IL17F genes were significantly associated with BMD. To our knowledge, this is the first report to examine these associations in a cohort of 200 Japanese women. ► IL6 and IL17F gene polymorphisms were significantly associated with BMD. ► This was the first study to find correlations between IL17F polymorphisms and BMD. ► The MTHFR gene polymorphism variant degrades bone quality and may increase BMD.